The Role, Modern Problems, And Development Prospects Of Metrological Support In Cultivating Melon Crops On Farms - Ru’ziboyev, Azamjon Dostonovich; Kurbanov, Abdurakhim Akhmedovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article explores the role and significance of metrological support in cultivating melon crops on farms. It highlights the importance of measuring instruments, such as refractometers, in ensuring product quality, rational resource use, and export competitiveness. The study discusses modern smart farming technologies and national standards, identifying key challenges. Furthermore, a newly developed method for assessing the technical condition and accuracy of measuring instruments used in agriculture is proposed.